The mathematical modeling system of voltage regulation train’s low-tension circles - Bilukhin, D. S. (Science and Transport Progress, 2011)
A mathematical model for research of the system of automatic voltage control of low-voltage circuits of electric locomotive with the generator power source supply is offered.